THE IMPLEMENTATION OF GOVERNMENT POLICY IN EMPOWERING BUSINESS AND "IRA-MASI" GROUP OF GIFT NILE TILAPIA (OREOCHROMIS SP.) FARMERS IN SUCO COM, EAST TIMOR - Valensa J.D. (Russian Journal of Agricultural and Socio-Economic Sciences, 2018)
Policy implementation is widely seen as the application of the legislation in which various actors, organizations, procedures, and techniques collaborate to implement policies in order to achieve policy goals or programs comprehended as a process, an output, and an impact (outcome). This study aims to identify and analyze the implementation of government policy in empowering the business and group of fish farmers, recognize the constraints faced by group of fish farmers, establish empowerment strategies that can be developed in empowering business and group of fish farmers, and determine the role of the government in empowering the wealth of fish farmer groups. This research was conducted in Com Village, Lautem Moro Subdistrict, Lautem District, East Timor, from December 15th, 2017, to February 5th, 2018. This research was conducted using qualitative descriptive method. Data collection used in this study was the primary and secondary data obtained using observation, interview, and documentation techniques.